Parer l’humain de divin - Thomas Galoppin (Cahiers Mondes Anciens, 2022)
In some Greek and Latin testimonies of Late Antiquity, several stones are used as core material in the making of different objects; these objects are described as jewels (body ornament) and as amulets (powerful objects). The texts in which the making of these garments is told include a divine empowerment of the objects. Three examples show how the divine adornment for mortal use is conceived. These cases are: 1. the pantarbe in a ring which, in Heliodorus’ Aethiopica, repels fire itself, 2. the isiac emerald in fibula that, in the Damigeron-Evax lapidary, gives charm to the wearer, and 3. the remaking of the kestos of the goddess Aphrodite by the Cyranides, around an obsidian stone and from the pattern of a divine diadem capable of emasculating men or even of changing gender assignment.